Analisis Cyberbullying pada Game Online Valorant: Studi pada Communication Abuse Antarpemain - Indrawan, Muhamad Wahfi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Competitive online games such as Valorant as a new medium that provides an interactive and competitive virtual space for online game players. Tension and excitement between players in competing often triggers the emergence of Cyberbullying behavior. Cyberbullying itself is the behavior of game players in the form of hate speech or negative actions that affect communication between online game players. However, researchers see that each player is different in responding to Cyberbullying carried out by other players and their teams. This study aims to find out how the factors, forms and responses of victims in doing, responding to communication abuse. The method in this study uses qualitative descriptive research. The results of the study show that Cyberbullying in the online game Valorant shows that the communication abuse factor is caused by other players who play badly, while the forms are carried out in the form of verbal through text or voice, as well as the response of the victims tends not to care and stay focused on the game to try to save it despite the bad treatment from other players.